Analisis Wacana Kritis Teun Van Dijk Tentang Pemberitaan RUU Penyiaran Di Detik Sumsel - Trio Zuliantino; Eni Murdiati; Muhammad Randicha Hamandia (CV. ITTC INDONESIA, 2024)
The development of the creative industry, various draft bills or broadcasting laws, is one of the focuses of attention. This bill was created with the aim of regulating various aspects of broadcasting, including regulation of the film industry. However, in the process of drafting and determining the articles, there was a gap in the emergence of various problems or issues that could affect industrial development in Indonesia. The broadcasting bill drafted by the DPR RI is the broadcasting bill dated 02 October 2023. The broadcasting bill consists of 14 chapters, to be precise on Monday, 27 May 2024, the process of drafting the text of the Revision of Law Number 32 of 2022 concerning Broadcasting (Broadcasting Bill) drew criticism from various circles, the problem formulation discussed is how the second media. Com constructs the discourse on the Broadcasting Bill in terms of text structure, social cognition and social context? And are there any practices of power that are behind or are revealed in the discourse structure of reporting on the broadcasting bill? . In this thesis, the research design used is qualitative descriptive research. Descriptive research is research to collect information regarding the status of an existing symptom, namely the situation according to the conditions at the time the research was carried out. The results of the superstructure analysis on the detik sumsel news media portal showed that the news writing met the requirements consisting of introduction, content and conclusion. . News can begin with a title that arouses other people's interest in reading, narrate an introduction that reflects some of the content of the news being conveyed, and reveal facts as discussion or content of the news, and close with criticism of the news that is being discussed. Then the microstructure in the news text shows that the news writer.